Perilaku Penggunaan Alat Pelindung Diri (APD) Pekerja Tenaga Kerja Bongkar Muat (TKBM) di PT. XYZ - Alfarizi, Ridwan Khafid; Ratriwardhani , Ratna Ayu; Ayu, Friska; Sunaryo, Merry (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT XYZ, a state-owned port services company, faces significant occupational health and safety risks, particularly for loading and unloading workers (TKBM), who often lack discipline in using personal protective equipment (PPE). This study aimed to assess TKBM workers' behavior regarding PPE usage. Utilizing a cross-sectional observational approach, the research surveyed 71 out of 249 TKBM workers. The findings indicate that most workers exhibit good PPE usage behavior. Despite this positive outcome, the research suggests enhancing PPE use through targeted training and briefings. Continuing efforts to bolster worker safety and PPE awareness are crucial for maintaining and improving safety standards in PT XYZ's loading and unloading work environments focusing on worker protection through the behavior of using PPE.